Quantum dynamical study of low-energy photoelectron bands of 2-phenylethyl-N,N-dimethylamine# - Gómez-Carrasco, Susana; Köppel, Horst (Journal of chemical sciences, 2012)
The first three photoelectron bands of 2-phenylethyl-N,N-dimethylamine (PENNA) are investigated theoretically, paying particular attention to the vibrational structure and to possible nonadiabatic coupling effects. A substantial vibronic interaction is established between the first and second excited cationic states (corresponding to the second and third photoelectron bands). Their coupling to the cationic ground state is found to be rather weak. This is tentatively attributed to the well-known fact that the latter carries a hole at the amine site, while the former two have the electron removed from benzene-type orbitals. The interaction between the two excited cationic states is characterized by a ‘hidden’ or local symmetry at the phenyl moiety. Preliminary dynamic calculations with two interacting electronic states and four vibrational modes are reported. The computed spectra are compared to experimental results of Weinkauf et al. Open image in new window Graphical Abstract Vertical ionization spectrum of PENNA along with the underlying orbitals are presented.
Im Titel ist das Rautenzeichen hochgestellt
Gesehen am 25.10.2018